2018
DOI: 10.1038/s41598-018-25990-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Direct and Indirect cold atmospheric-pressure plasma methods in the B16F10 melanoma cancer cells treatment

Abstract: In this study a novel method was implemented and investigated in order to destroy cancer cells inside the mouse body on a clinical level. In the case of in-vitro study, MTT assay was employed to discover an effective dose of applied plasma and distinguish the plasma effect in direct and in indirect treatments. Tumor growth was also measured in in-vivo section so that the effectiveness of direct and indirect treatments could be compared. Furthermore, an investigation was conducted to study the interferences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 72 publications
5
86
1
2
Order By: Relevance
“…Xiang L et al reported that PAM could selectively reduce the cell viability of triple negative breast cancer cells 23 . Cell death was also induced by treatment with PAM in other types of cancers, including pancreatic cancer, glioblastoma, squamous head and neck cancer, and melanoma [24][25][26] . These authors presumed that the underlying mechanism of cell death was related to increased apoptosis through the accumulation of intracellular reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…Xiang L et al reported that PAM could selectively reduce the cell viability of triple negative breast cancer cells 23 . Cell death was also induced by treatment with PAM in other types of cancers, including pancreatic cancer, glioblastoma, squamous head and neck cancer, and melanoma [24][25][26] . These authors presumed that the underlying mechanism of cell death was related to increased apoptosis through the accumulation of intracellular reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…5a and b). 75,94 Thus, the CAP treatment in vitro cannot simply be expressed as the treatment by a specific long-lived reactive species, such as H 2 O 2 -treatment, NO 2 À -treatment, NO 3 À -treatment, or ONOO À -treatment.…”
Section: Direct Treatment Vs Indirect Treatmentmentioning
confidence: 99%
“…The half-life of many types of ROS is short, and the current concept is that it is not necessarily the plasma-derived ROS that are directly interacting with cells and tissues but rather secondary molecules derived from primary ROS as well as oxidative modifications on organic molecules [12]. When applied at higher doses, these ROS overcome the capacity of tumor cells and activate different cell signaling pathways that culminate in cell death [13,14]. Besides its cytotoxic effect, cold plasma has been described as a potent inducer of the immunogenic cancer cell death (ICD) [15,16].…”
Section: Introductionmentioning
confidence: 99%